Electrochemical Method for the Design of New Possible Gadolinium-Based Contrast Agents - Claudia Carbone; Aaron Stoeckle; Manuel Minardi; Fulvio Uggeri; Luciano Lattuada; Alessandro Minguzzi; Alberto Vertova (Nanomaterials)
Magnetic resonance imaging (MRI) is a technique that employs strong magnetic fields and radio frequencies to generate detailed images of the body’s interior. In oncology patients, gadolinium-based contrast agents (GBCAs) are frequently administered to enhance the visualization of tumors. Those contrast agents are gadolinium chelates, characterized by high stability that prevents the release of the toxic gadolinium ion into the body. This work is part of the research for alternative nanoscaled GBCAs. Following the synthesis and characterization of zinc hexacyanoferrate nanoparticles, gadolinium ions were successfully incorporated into a hexacyanoferrate-based matrix, deposited on FTO-coated glass used as working electrode in a gadolinium salt solution, by applying a fixed potential determined through cyclic voltammetry studies. The presence of gadolinium inside the matrix was confirmed by EDX.